Epigenetic and developmental influences on the risk of obesity, diabetes, and metabolic syndrome - Smith CJ (Dove Medical Press, 2015)
Caitlin J Smith, Kelli K Ryckman Department of Epidemiology, University of Iowa, College of Public Health, Iowa City, IA, USA Abstract: Metabolic syndrome is a growing cause of morbidity and mortality worldwide. Metabolic syndrome is characterized by the presence of a variety of metabolic disturbances including obesity, hyperlipidemia, hypertension, and elevated fasting blood sugar. Although the risk for metabolic syndrome has largely been attributed to adult lifestyle factors such as poor nutrition, lack of exercise, and smoking, there is now strong evidence suggesting that predisposition to the development of metabolic syndrome begins in utero. First posited by Hales and Barker in 1992, the “thrifty phenotype” hypothesis proposes that susceptibility to adult chronic diseases can occur in response to exposures in the prenatal and perinatal periods. This hypothesis has been continually supported by epidemiologic studies and studies involving animal models. In this review, we describe the structural, metabolic and epigenetic changes that occur in response to adverse intrauterine environments including prenatal and postnatal diet, maternal obesity, and pregnancy complications. Given the increasing prevalence of metabolic syndrome in both the developed and developing worlds, a greater understanding and appreciation for the role of the intrauterine environment in adult chronic disease etiology is imperative. Keywords: epigenetics, metabolic syndrome, fetal programming, maternal, pregnancy complications